The Role of Self-Efficacy in The Career Maturity of College Students With Disabilities : A Systematic Literature Review - Muthya Firagil Restuti; Muchamad Irvan; Umi Safiul Ummah; Dimas Arif Dewantoro; Anggita Hemaylia Putri (Journal of Educational Learning and Innovation (ELIa), 2025)
This study aims to analyze and synthesize empirical evidence regarding the role of self-efficacy in career maturity among students with disabilities, a group that faces double challenges in the transition from education to the world of work. This study uses the systematic literature review (SLR) method with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The search was conducted in major academic databases using strict inclusion and exclusion criteria, resulting in only three primary articles that were eligible for synthesis. The findings consistently show that self-efficacy plays a central and positive role in the career maturity of students with disabilities, both directly and through interaction with mediating and moderating variables such as resilience, intrinsic motivation, self-advocacy, and social support. The limited number of studies in this review restricts the generalizability of the findings. Further studies covering a more diverse range of contexts are needed to strengthen the conclusions.